Biossorção dos íons Ni2+ e Cu2+ pela biomassa Sargassum sp. imobilizada - Barquilha, Carlos Eduardo Rodrigues (2015)
Heavy metals such as nickel e copper, when released on water resources are potencial sources of pollution of the environment. Usually, the methods used for waste treatment contains metals, when not expensive, doesn't reach the discharge standards determined by environmental legislation. The search for alternative methods has showed that biosorption presents high metal holding capacity combined with low cost. To use this process in industrial scale mechanisms have been proposed, including immobilization, because of the difficulty working with biomass in narute and free-living particles in continuous system, as fixed-bed column. Thus, the aim of this study was evaluate the effect of immobilization of Sargassum sp. seaweed in alginate beads using drip method in biosorption of nickel and copper. Experiments in batch systems, kinetic and equilibrium studies, were performed for free and immobilized Sargassum sp. and calcium alginate using single-component solutions of nickel and copper. Where were adjusted for kinetic models, pseudo first-order and second-order, and equilibrium modeling, Langmuir and Freundlich isotherms. The results showed that immobilization didn't influence significantly the kinetics of biosorption, while the biosorption capacity increased with immobilized Sargassum sp., emphasizing the potential biosorption of calcium alginate. Equilibrium data of immobilized Sargassum sp. can be represented by the Langmuir isotherm with á and ,, equal to 61,89 mgNi g-1 and 0,019 L g-1 for nickel and 113,22 mgCu g-1 and 0,077 L g-1 for copper. While for free Sargassum sp. were of 53,57 mgNi g-1 and 0,028 L g-1 and 94,35 mgCu g-1 and 0,068 L g-1, respectively. Dynamic studies were also performed in fixed-bed column, in which immobilized biomass obtained higher uptake and wasn't affected by low porosity..